1984
DOI: 10.2190/m6xl-x8x0-ex6g-7ar8
|View full text |Cite
|
Sign up to set email alerts
|

Social Well-Being of Institutionalized Elderly Persons

Abstract: This article describes the development of a scale, the Social Well-Being Scale, to measure the extent to which institutionalized older persons perceive their social needs as being met. For persons over sixty-five years of age, the scale score is not affected by age or sex, but it does distinguish them by race, health, and type of living arrangement. Further, the Social Well-Being Scale predicts the level of psychological well-being.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
2

Year Published

1989
1989
2002
2002

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 2 publications
0
7
0
2
Order By: Relevance
“…-In brief, much of the past work on social involvement has focused on community-dwelling men and women and has measured outcomes such as social ties (Brook et al, 1983) and frequency of contacts with friends and relatives (Willey and Silliman, 1990). In the nursing home setting, Reid and Washington (1984) measured the degree to which the social needs of residents were being met, whereas other evaluation methods have focused on negative social behaviors (Gurel, Linn, and Linn, 1972;Wilkinson and Graham-White, 1980). Mor and colleagues' study (1995) of social engagement addressed the need for a means to measure residents' ability to take advantage of opportunities for social interaction in the nursing home setting.…”
mentioning
confidence: 99%
“…-In brief, much of the past work on social involvement has focused on community-dwelling men and women and has measured outcomes such as social ties (Brook et al, 1983) and frequency of contacts with friends and relatives (Willey and Silliman, 1990). In the nursing home setting, Reid and Washington (1984) measured the degree to which the social needs of residents were being met, whereas other evaluation methods have focused on negative social behaviors (Gurel, Linn, and Linn, 1972;Wilkinson and Graham-White, 1980). Mor and colleagues' study (1995) of social engagement addressed the need for a means to measure residents' ability to take advantage of opportunities for social interaction in the nursing home setting.…”
mentioning
confidence: 99%
“…Lawton (1972) found no correlation between morale and age (confirmed by several authors, eg Wenger, 1984b;Diener, 1984;Liang and Bollen, 1986), gender or marital status. Using a Social WellBeing Scale with institutionalized elderly people, Reed and Washington (1984) also found no correlation with age or gender. Environmental factors, such as food, neighbours and economic status, were also found to be unrelated to morale (Lawton, 1972).…”
Section: Discussionmentioning
confidence: 81%
“…The findings of Maddox (1963) and Lawton (1972) suggest that morale may be an unstable measure. It has been suggested that multidimensional measures may be more stable over time than less reliable single-variable measures and that for this reason they may be less appropriate for mea- Maddox, 1963;Blau, 1973;Maas and Kuypers, 1974;Larson, 1978;Chibucos, 1984;Klemmack and Roff, 1984;Reed and Washington, 1984;Cattell, 1988;Parmalee et al, 1991, Bowling and Browne, 1991Levin, 1964Zung, 1967;Holahan and Moos, 1981;Cattell, 1988 Cumming andHenry, 1961;Kutner, 1962;Maddox, 1963;Lehr, 1981;Isshii-Kurtz, 1990 Lowenthal andHaven, 1968;Gubrium, 1972;Blau, 1973;Brown and Harris, 1978;Ho et al, 1988 Gifford andGolde, 1978;Stephens et al, 1978;Lawton, 1980Gubrium, 1972Blau, 1973;Creecy, 1976;Lawton, 1980;Lehr, 1981;Quinn et al, 1984;Wenger, 1990 Stephens et al, Henderson, 1981;Holahan andMoos, 1981 Dowd andLa Rosa, 1982;Scott and Roberto, 1984;…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For this purpose, observations of the daily routine in six institutions were recorded at various times. Questionnaires were distributed to all residents capable of responding, measuring autonomy and mastery feelings according the scale developed by Lemke and Moos (1987) and well-being according to the scale developed by Reed and Washington (1984). The same questionnaires also were distributed to the residents' families and to selected personnel in the various departments (indeIn-Service Training 589 pendent, frail, and nursing) of each institution.…”
Section: Training Project For Institutional Workersmentioning
confidence: 99%